Organization Cultures for Administration of Muang Suang School under Roi Et Elementary Education Service Area Office 2 - Boonbanlu, Chuchart; Thinsaendee, Theeraphat; Ladawan, Krityakorn (Academic Journal of Mahamakut Buddhist University Roi Et Campus, 2019)
The objectives of the research article were to 1) carry out the study on bringing organizational cultures as dependent variables into use for administrations of Muang Suang district-located schools, 2) draw comparisons between independent variables and dependent variables. 3) examine problems and suggestions for enhancing such administrations. The target groups with the limited number of subject were 181 school personnel under the above office in Muang Suang district. The data device was the questionnaire. Data were processed with the computer software package to find frequencies, percentages, means, standard deviations, t-tests and F-tests (One-way ANOVA). The results of findings were as follow : 1. The level of bringing organizational cultures into use for administrations of the target schools has been comprehensively rated at the high scale in every culture. 2. Comparisons of data between both variables have shown no significant differences in both comprehensive and individual cultures, whereas their years of work experiences have proven otherwise in both cultures with the statistical significance at .05 level, except for clan culture. 3. Problematic states of organizational cultures at the target schools in the district are of three issues. 1) Budget allocation for securing instructional media and materials does not suffice to teachers’ requirements. 2) Teachers neglect evolution of state-of-the-art technologies, leaving them behind to keep pace with their work systems. 3) Divisions of personnel’s responsibilities and tasks are unequal, not matching up with their knowledge and competence. As a result, personnel cannot achieve some targets of their undertakings as planned. Suggestions are: 1) tasks ought to be equally divided and matched up with individual knowledge and competence, 2) organizational cultures in their schools have to be adjusted in accordance with current situations, and 3) Some organizational cultures would have focused on unity, responsibilities, hospitality and generosity to support school jobs to be more effective.